An uncommon dermatophyte infection: two cases of cutaneous infection with Trichophyton verrucosum. (1st June 2015) - O'Gorman, S. M.; Britton, D.; Collins, P.
Summary: Zoophilic dermatophytes can cause highly inflammatory cutaneous infections. Cattle represent the largest reservoir for the zoophilic dermatophyte Trichophyton verrucosum . Effective vaccination programmes have contributed to a low rate of livestock infection in central and northern Europe, and T. verrucosum infection is relatively more common in southern Europe and in Arabic countries. Transmission to humans typically results from direct contact with infected livestock. It may also be transmitted from person to person. We report two cases of T. verrucosum skin infections in Irish farmers. In both cases, effective treatment was delayed due to misdiagnosis of the condition as a bacterial infection in the primary care setting. Both cases responded rapidly to treatment with oral terbinafine. Culture of T. verrucosum can take 3 weeks or longer to grow, therefore a high index of clinical suspicion is necessary, and skin scrapings for potassium hydroxide microscopy and culture are essential for accurate diagnosis.